THE RELATED OF PERSONAL HYGIENE AND CONTACT FREQUENCY WITH CONTACT DERMATITIS COMPLAINTS IN MOTORBIKE WASHING WORKERS IN JEBRES AND MOJOSONGO SURAKARTA DISTRICTS - Rinawati, Seviana; Wulandari, Sri Mustika (Faculty of Vocational Studies, Universitas Airlangga, 2020)
Backgroud : Motor vehicle wash is an activity that comes in direct contact with chemicals,one of the risks is allergic to contact dermatitis complaints. The factors that influence complaints of contact dermatitis are Personal hygiene and the frequency of contact of motor vehicle washing workers. Purpose : This study aims to determine the relationship between personal hygiene and the frequency of contact with complaints of contact dermatitis. Method: This study was an observational analytic study, with a cross-sectional design. Respondents from the study were motor vehicle washing workers in Jebres and Mojosongo Surakarta with 35 respondents from 60 workers. The sampling technique uses purposive sampling. This study used a questionnaire base on the title and analyzing data uses the Somers' test and the Logistic Regression test. Result: The Somers' correlation test results showed a significant relationship between personal hygiene and complaints of contact dermatitis with a p-value of 0.000, the direction of correlation (-), and a correlation coefficient of 0.662. The test results also showed a significant relationship between the frequency of contact with complaints of contagious dermatitis with a p-value of 0.000, the direction of correlation (+), and the correlation coefficient 0.726. The results of the logistic regression test showed that the contact frequency variable had the most influence on complaints of contact dermatitis with an odds ratio of 28,078. Conclusion: There is a significant relationship between personal hygiene and the frequency of contact with complaints of contact dermatitis.